(untitled) (Iraqi Journal of Civil Engineering, 2024)
A voided slab is an innovative type of reinforced concrete slab system developed recently, that has proven its excellence in terms of its structural, environmental, and economic benefits. The self-weight of a slab can be considerably reduced using different shapes of void formers like spherical, cubical, and donut. All researchers confirm that the self-weight of the slab decreases by up to 40%. Various researchers have carried out experimental and numerical studies for studying one-way flexural strength and punching shear strength of voided reinforced concrete slabs. However, the one-way or two-way flexural strength of the voided slab still needs to be acutely investigated. This paper deals with the survey on many titles of selected high impacted journals to illustrated almost criteria of investigations of these types of slabs. The main outcomes of this paper are the term environmental protection, sustainable and plastic waste reduction had a role not a little in this research, as 16% of the research on this topic were studied. Also, the plastic material governs the subject of the raw materials used to make the voids;43% of researches used this material.